Unraveling the drug distribution in brain enabled by MALDI MS imaging with laser-assisted chemical transfer - Shuai Guo; Kening Li; Yanwen Chen; Bin Li (Elsevier, 2022)
Accurate localization of central nervous system (CNS) drug distribution in the brain is quite challenging to matrix-assisted laser desorption/ionization (MALDI) mass spectrometry imaging (MSI), owing to the ionization competition/suppression of highly abundant endogenous biomolecules and MALDI matrix. Herein, we developed a highly efficient sample preparation technique, laser-assisted chemical transfer (LACT), to enhance the detection sensitivity of CNS drugs in brain tissues. A focused diode laser source transilluminated the tissue slide coated with α-cyano-4-hydroxycinnamic acid, an optimal matrix to highly absorb the laser radiation at 405 nm, and a very thin-layer chemical film mainly containing drug molecule was transferred to the acceptor glass slide. Subsequently, MALDI MSI was performed on the chemical film without additional sample treatment. One major advantage of LACT is to minimize ionization competition/suppression from the tissue itself by removing abundant endogenous lipid and protein components. The superior performance of LACT led to the successful visualization of regional distribution patterns of 16 CNS drugs in the mouse brain. Furthermore, the dynamic spatial changes of risperidone and its metabolite were visualized over a 24-h period. Also, the brain-to-plasma (B/P) ratio could be obtained according to MALDI MSI results, providing an alternative means to assess brain penetration in drug discovery.